Typhoid Conjugate Vaccines and Enteric Fever Control: Where to Next?. (29th July 2020) - Steele, A Duncan; Carey, Megan E; Kumar, Supriya; MacLennan, Calman A; Ma, Lyou-Fu; Diaz, Zoey; Zaidi, Anita K M
Abstract: After the unprecedented success and acceleration of the global agenda towards typhoid fever control with a strong World Health Organization recommendation and the approval of funding from Gavi, the Vaccine Alliance (Gavi), for the use of a new typhoid conjugate vaccine (TCV), we should turn our minds to the challenges that remain ahead. Despite the evidence showing the safety and clinical efficacy of TCV in endemic populations in developing countries, we should remain vigilant and explore hurdles for the full public health impact of TCV, including vaccine supply for the potential global demand, immunization strategies to optimize the effectiveness and long-term protection provided by the vaccines, potential use of TCV in outbreak settings, and scenarios for addressing chronic carriers. Finally, challenges face endemic countries with poor surveillance systems concerning awareness of the need for TCV and the extent of the issue across their populations, and how to target immunization strategies appropriately.